2001
DOI: 10.1002/path.996
|View full text |Cite
|
Sign up to set email alerts
|

Activated status of tumour‐infiltrating lymphocytes and apoptosis in testicular seminoma

Abstract: Testicular seminoma is characterized by a prominent lymphoid infiltrate and an excellent prognosis. Cytotoxic T-lymphocytes (CTLs) infiltrating seminoma tumour nests constitute a major subset of the lymphoid infiltrate. The objective of this study was to determine whether CTLs express markers of cytotoxic potential and activity and whether the number of activated CTLs correlates with the extent of apoptosis in testicular seminomas, as opposed to non-seminomatous testicular germ cell tumours (NSTGCTs). Twenty c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…Tumor-infiltrating lymphocytes correlate directly with better seminoma prognosis (4,7,24,25). For men with HIV/AIDS, we found that seminoma risk was significantly higher for disseminated than for earlier stages.…”
Section: Discussionmentioning
confidence: 48%
“…Tumor-infiltrating lymphocytes correlate directly with better seminoma prognosis (4,7,24,25). For men with HIV/AIDS, we found that seminoma risk was significantly higher for disseminated than for earlier stages.…”
Section: Discussionmentioning
confidence: 48%
“…The infiltration of a tumor with various immune cells has been correlated with increased host survival and decreased metastases of the cancer in some instances [12][13][14][15][16] although this is not the case for all cancers [17,18]. Studies have demonstrated that high levels of tumor infiltrating lymphocytes (TILs) are a feature associated with MSI-H colorectal cancer [19,20].…”
mentioning
confidence: 99%
“…The role of the immune response in controlling metastatic events has been well-described [12][13][14][15]. The infiltration of a tumor with various immune cells has been correlated with increased host survival and decreased metastases of the cancer in some instances [12][13][14][15][16] although this is not the case for all cancers [17,18].…”
mentioning
confidence: 99%
“…Natural killer cells are virtually absent in endometrial tumors (11). Activated CTLs expressing TIA-1 and/or granzyme B cytotoxic granules have been demonstrated in certain human neoplasms, such as EBV-associated gastric cancer, medullary carcinoma of the breast, germ cell tumors of the testis, and carcinomas of the colon, cervix, esophagus, and kidney (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%